Pengayaan Mie Basah dengan Substitusi Tepung Kacang Merah dan Tepung Ubi Jalar Ungu - Pakhri, Asmaruddin; Wahyuni, Sri; Hartono, Rudy; Zakaria, Zakaria (Media Gizi Pangan, 2021)
Indonesian people consume a lot of noodles because this food is filling, easy to make, the taste is acceptable to all circles and the price is more economical. According to Riskesdas 2018, consumption of noodles in Indonesia is on average 1-6 times per week. The importance of food diversification so that food is not dominated by one or a few food ingredients, among others, by making products using various types of local food.This study aims to determine the acceptability and protein content and fiber of wet noodles with the substitution of red bean flour and purple sweet potato flour. The research design was pre-experimental conducted in the laboratory. Acceptance using hedonic test of 25 panelists. The protein and fiber content of wet noodles was calculated using the Food Composition Table, then presented in the form of tables and narratives.The results of the study based on the Friedman test from the most preferred color aspect, namely the concentration of O2B with 10% red bean flour substitution and 10% purple sweet potato flour, the most preferred aroma aspect was the O3C concentration with 10% red bean flour substitution and 30 purple sweet potato flour. %, and the most preferred texture and taste aspects were the concentration of O4D with the substitution of 15% red bean flour and 20% purple sweet potato flour. The results of the analysis of protein content showed that the highest concentration of red beans was 15% and sweet purple sweet potato flour 20% (14.38 grams in one recipe and 5.75 grams/100 grams) and the highest fiber content was 10% red bean flour and flour. 30% purple sweet potato (4.59 grams in one recipe and 1.84 grams/100grams).It is recommended that in the manufacture of wet noodles measure the water content of red bean flour and purple sweet potato flour to comply with SNI and make dry noodles so that they have a long shelf life so that they can be marketed